2020
DOI: 10.2174/1573401315666181218151541
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Zataria multiflora and Ocimum basilicum on Escherichia coli O157:H7 During Ripening of Traditional Lighvan Cheese

Abstract: Background: Escherichia coli O157:H7 is one of the most common causes of contamination in Lighvan cheese processing. Using from natural antimicrobial essential oils is applied method to decrease the rate of microbial contamination of dairy products. The present investigation was done to study the antimicrobial effects of Z. multiflora and O. basilicum essential oils on survival of E. coli O157:H7 during ripening of traditional Lighvan cheese. Methods: Leaves of the Z. multiflora and O. basilicum plants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…In particular, EO of Zataria multiflora strongly inhibited all the E. coli strains. Our results agree with other authors who have shown that Zataria multiflora EO had an inhibitory effect on growth of E. coli O157 in white-brined cheese and in traditional Lighvan cheese [35].…”
Section: Discussionsupporting
confidence: 93%
“…In particular, EO of Zataria multiflora strongly inhibited all the E. coli strains. Our results agree with other authors who have shown that Zataria multiflora EO had an inhibitory effect on growth of E. coli O157 in white-brined cheese and in traditional Lighvan cheese [35].…”
Section: Discussionsupporting
confidence: 93%
“…can reduce the risk of foodborne bacteria and especially E. coli in food products. 26 Also, Abramovic et al reported the antioxidant potential (AOP) and effects of Zataria multiflora, especially against bacteria such as Staphylococcus aureus, Listeria monocytogenes, Campylobacter jejunum, which is compatible with our study's findings. 27 According to Osanloo et al carvacrol and thymol are the main components of ZM which produce antimicrobial effects against fungus, E. coli, and S. aureus Zomorodian supported the idea of using ZM in mouthwashes and denture cleansers since they show high efficacy in inhibiting microbial strains.…”
Section: Discussionsupporting
confidence: 92%